2008
DOI: 10.1089/jwh.2007.0417
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Premenstrual Dysphoric Disorder on Health-Related Quality of Life

Abstract: PMDD is associated with substantial burden on both physical and mental aspects of HRQoL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 37 publications
0
64
0
2
Order By: Relevance
“…This result is in agreement with previous studies showing that severe PMS/PMDD symptoms negatively affect QOL. [10][11][12][38][39][40] Some limitations of the present study must be addressed. First, we relied on self-reported information to exclude women with any physical or psychiatric comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in agreement with previous studies showing that severe PMS/PMDD symptoms negatively affect QOL. [10][11][12][38][39][40] Some limitations of the present study must be addressed. First, we relied on self-reported information to exclude women with any physical or psychiatric comorbidity.…”
Section: Discussionmentioning
confidence: 99%
“…Sixth, Yang M, et al (2008) [24] conducted a study about burden of premenstrual dysphoric disorder on health-related quality of life among USA women via internet survey. They concluded that CSPMS had significant impact on the physical wellbeing among their participants especially those who had chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…PMDD has a significant negative impact on quality of life. Yang et al reported that the burden of PMDD on health-related quality of life was greater than the burden associated with back pain, and was similar to Type II diabetes, hypertension, rheumatoid arthritis and somewhat similar to depression [18]. Heinemann, Minh, Filonenko, and Uhl-Hochgraber concluded that PMDD is associated with impaired work productivity and absenteeism, thus resulting in a potential reduction of female economic productivity (19).…”
Section: The Burden Of Illnessmentioning
confidence: 99%